Supporting language learning with TTS voice output integrated into epub e-books - Achmad Suyono; Bambang Suryanto (UPT P2M Politeknik Negeri Malang, 2016)
Text-to-speech (TTS) technology gains more popularity nowadays as computer and smart devices are becoming affordable and widely used. The adoption of this technology in language learning is also increasing. With the rise of mobile learning, an attempt to integrate this technology in EPub e-books is proposed. It is expected that the e-books incorporating TTS technology voice output can help teachers to efficiently produce and distribute learning materials, to reduce workload in dealing with individual students’ learning problems, to implement necessary learning guidance, to provide distraction-free mobile language learning materials, and to be more productive with technology to promote a better language learning in the students’ daily activities.